Diffuse cardiac fibrosis quantification in early systemic sclerosis by magnetic resonance imaging and correlation with skin fibrosis. Issue 2 (June 2018) - Lee, Daniel C; Hinchcliff, Monique E; Sarnari, Roberto; Stark, Madeline M; Lee, Jungwha; Koloms, Kimberly; Hoffmann, Aileen; Carns, Mary; Thakrar, Anjali; Aren, Kathleen; Varga, John; Aquino, Alejandro; et al.
Purpose: To evaluate the utility of cardiac magnetic resonance T1 mapping in early systemic sclerosis and its association with skin score. Methods: In total, 24 consecutive patients with early systemic sclerosis referred for cardiovascular evaluation and 12 controls without systemic sclerosis were evaluated. All patients underwent cine, T1 mapping, and late gadolinium–enhanced cardiac magnetic resonance imaging. T1 mapping indices were compared between systemic sclerosis patients and controls (extracellular volume fraction, gadolinium partition coefficient (λ), pre-contrast T1, and post-contrast T1). The association between T1 mapping parameters and the modified Rodnan skin score was determined. Results: There were no significant differences in cardiac structure/function between systemic sclerosis patients and controls on cine imaging, and 8 of 24 (33%) systemic sclerosis patients had evidence of late gadolinium–enhanced cardiac magnetic resonance imaging (i.e. focal myocardial fibrosis). Of the T1 mapping parameters (indices indicative of diffuse myocardial fibrosis), extracellular volume fraction differentiated systemic sclerosis patients from controls the best, followed by λ, even when the eight systemic sclerosis patients with late gadolinium–enhanced cardiac magnetic resonance imaging were excluded. Extracellular volume fraction had a sensitivity and specificity of 75% and 75% for diffuse myocardial fibrosis (optimal abnormal cutoff value of >27% (area under receiver operating characteristic curve = 0.85)). In the 16 patients without evidence of late gadolinium–enhanced cardiac magnetic resonance imaging, each of the four cardiac magnetic resonance T1 mapping parameters (extracellular volume fraction, λ, Pre-T1 and Post-T1) correlated with modified Rodnan skin score ( R = 0.51–0.65, p = 0.007–0.043), indicating a correlation between systemic sclerosis cardiac and skin fibrosis. Conclusion: The four T1 mapping indices are significantly correlated with modified Rodnan skin score in patients with early systemic sclerosis. Quantification of diffuse myocardial fibrosis using extracellular volume fraction should be considered as a marker for cardiac involvement in systemic sclerosis clinical studies.